ISSUES OF ATTRACTING FOREIGN INVESTMENTS TO THE SPECIAL ECONOMIC ZONES OF THE COUNTRY - Oltaev, Shavkat (Innovative Development in Educational Activities, 2024)
A special economic zone or free economic zone is a limited territory with a special legal status compared to the rest of the country. Often, special status is expressed in preferential tax or customs conditions for national or foreign entrepreneurs. The main purpose of creating such zones is to solve the problems of socio-economic development of the state, individual regions or sectors. The article covers the issues of attracting foreign investments to the special economic zones of our country.